Effective porosity in groundwater flow analysis for fractured sedimentary rocks: Case studies of the Koetoi and Wakkanai formations in Horonobe, Hokkaido, Japan - MIYAKAWA, Kazuya; IMAI, Hisashi; NAKATA, Kotaro; OHNO, Hirokazu; HASEGAWA, Takuma; ISHII, Eiichi; HIRAI, Satoru (Journal of Nuclear Fuel Cycle and Environment, 2024)
Groundwater flow analysis is used to evaluate groundwater travel times and pathways over several kilometers to several tens of kilometers, covering the entire groundwater recharge and discharge areas, during preliminary investigations for a potential repository for high-level radioactive waste. A rock's hydraulic effective porosity (kinematic porosity) is a sensitive parameter while analytically determining the travel time of groundwater in the fractured rock. However, the concept of kinematic porosity in fractured sedimentary rock is unclear. For example, the permeability of fractures obtained from in-situ hydraulic packer tests in borehole investigations is treated as the permeability of the rock, while the porosity of the intact rock obtained from other tests is treated as the kinematic porosity. In this study, we examined the method to estimate the kinematic porosity of fractured sedimentary rock by comparing the travel time using the kinematic porosity estimated based on the fracture aperture and intact rock’s porosity with the observation results, using the Koetoi Formation and Wakkanai Formation (shallower part), which are sedimentary rocks with fracture development in low-permeability rock matrix, as an example. The travel time was consistent with the observations when the kinematic porosity was estimated based on the fracture aperture; the kinematic porosity was one to three orders of magnitude smaller than the porosity in the intact rock. In the case of sedimentary rocks with a water-conducting-fracture network in low-permeability rock matrix, it was shown that estimating the kinematic porosity based on the fracture aperture width is effective.